MAGIC REALISM IN QUEEN OF THE SPARROWS SHORT STORY BY JANET E. IRVIN - PAMBUDI, NOVIAWAN KUSUMA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Magic Realism, Magic realism’s elements, myth, Queen of the Sparrows, short story. Literature is part of life since the story which is appointed in the literary works is influenced by life phenomenon. One of life phenomenon happening in reality is theoccurrence of magical thing. Magic realism is a narrative style created to narratemagical thing or fantasy in the reality. Magic realism is unique since it is an oxymoron or a term which is built by two contradiction words. The word “Magic” signifies an extra ordinary or fantasy while the word “Realism” signifies reality or world with nothing of fantasy. This research aims to find out the magic realism’s elements and what is the correlation of each element in constructing magic phenomenon in the reality.  This research uses the concept of magic realism’s elements by Faris to reveal the magic realism’s element employed by the author in Queen of the Sparrows shortstory and a concept of defocalization to reveal the correlation of those elements inconstructing magic phenomenon in reality through the author’s point of view. Then,those concepts will lead the discussion about the magic realism’s element in Queen ofthe Sparrows short story.  In this short story, the author transforms herself in the narration and character’s dialogues toward the existence of Amrita’s magical experience in the story. It can be seen in the finding and discussion such as irreducible element of Amrita’s magical experience, the detail description of the phenomenal world used as background of the occurrence of Amrita’s magical experience, unsettling doubts in the Merit’s role toward Amrita’s magical experience that lead the readers’ hesitation, merging realms of Merrit’s modern rationality and Victor’s traditional myth in the naming of Amrita, and disruption of time, space, and identity toward Amrita as an ordinary girl who is experiencing magical event. Then, those five elements are established to construct magic realism of the story. For the next researchers who want to look for new object to be analyzed, they are extremely suggested to use magic realism in other kinds of narrative fiction sincemagic realism is a unique concept in the narrative fiction as the modes and themesbecause there are two contradictory world blended in the story.